Eeffect of loading rate on fracture of NiTi - Mutlu, Fatma. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
This thesis studies the e ect of loading rate on fracture behavior of Shape Memory Alloy (SMA) NiTi. First, Di erential Scanning Calorimetry (DSC) are used to obtain the phase transformation temperatures of NiTi. Then series of tensile tests are performed for determining the mechanical properties under di erent loading rates. Next, fracture tests under increasing loading rates are conducted using pre-cracked, Mode-I Compact Tension (CT) specimens and critical stress intensity factors are calculated using the empirical equations proposed by ASTM E399 assuming that Linear Elastic Fracture Mechanics (LEFM) is applicable. Then, displacement eld obtained with the Digital Image Correlation (DIC) technique is used for stress intensity factor (SIF) calculations. Phase transformation region extension along the crack is estimated with DIC measurements and is compared to the analytical calculations. Analytical calculations for phase transformation region size are carried out using SIFs obtained from DIC and from the empirical equations of ASTM E399. Finally, using material properties obtained from tensile tests and the results of fracture tests, Finite Elements (FE) models are built to calculate the phase transformation regions. Using the J contour integrals, stress intensity factors are estimated using LEFM relations. Using the displacement eld obtained from the FE models, SIF values are calculated and the Crack Mouth Opening Displacement (CMOD) values are obtained from the FE models.
Keywords: Shape memory alloys.